The angular power spectrum measurement of the Galactic synchrotron emission using the TGSS survey. Issue Volume 12:Issue S333(2017) (8th May 2018) - Choudhuri, Samir; Bharadwaj, Somnath; Ali, Sk. Saiyad; Roy, Nirupam; Intema, H. T.; Ghosh, Abhik
Abstract: Characterizing the diffuse Galactic synchrotron emission (DGSE) at arcminute angular scales is needed to remove this foregrounds in cosmological 21-cm measurements. Here, we present the angular power spectrum ( C ℓ ) measurement of the diffuse Galactic synchrotron emission using two fields observed by the TIFR GMRT Sky Survey (TGSS). We apply 2D Tapered Gridded Estimator (TGE) to estimate the C ℓ from the visibilities. We find that the residual data after subtracting the point sources is likely dominated by the diffuse Galactic synchrotron radiation across the angular multipole range 240 ≤ ℓ ≲ 500. We fit a power law to the measured C ℓ over this ℓ range. We find that the slopes in both fields are consistent with earlier measurements. For the second field, however, we interpret the measured C ℓ as an upper limit for the DGSE as there is an indication of a significant residual point source contribution.